Minimization of Emergency Response Time by Incorporating Aerial Transportation - Banar, Mahdi (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In this thesis, we deal with two different real-life medical emergency service problems. In these problems, we consider a city in which the locations of all the hospitals, medical service centers, and the other emergency care centers are known. In both problems the emergency services are deployed using aerial and ground vehicles for moving towards patients in their locations after receiving a call, performing the initial emergency medical care, and transporting the patients to the hospitals or other medical care facilities. For this reason, the accidents or demands are classified into two types the severity accidents which need aerial vehicles and normal accidents which are operated by ground vehicles. According to the average number of the accidents in each location (node) and the severity of the accident, a weight is assigned to each node. In the first problem, we assume that the ground emergency services are optimal and we just deal with assigning a given number of the aerial vehicles to the hospitals or the medical care centers for the severity accidents or emergency medical demands in a way that the total response time by the aerial vehicles is minimized. In another words, this type of the demands for ground and aerial services are different in this type of the problem. In the second problem, we are dealing with both ground and aerial medical services together and at the same time. As the number of the accidents or the demands for both ground and aerial services are known and separate. In this type of the problem we are aiming to assign a given number of the aerial and ground vehicles to the hospitals or the medical care centers in a way that the total response time by all the aerial and ground vehicles is minimized.

ÖZ: Bu tezde, iki değişik sıhhi acil servis problemi incelenmiştir. Bu problemlerde bahis konusu şehirdeki tüm hastane, sıhhi servis merkezleri ile diğer acil yardım merkezlerinin bulundukları mahallerin bilindiği varsayılmıştır. Her iki problemlerde de acil servis için telefonla talep alınmasını takiben hava veya kara ambulansının atanması ile başlayan süreç, olay mahallinde verilen ilk yardımı takiben hastanın hastane veya diğer bir sıhhi bakım merkezine naklini içerir. Bu gayeyle, talepler olayın ciddiyetine göre iki guruba ayrılarak, çok acil vakalara hava ambulansı, çok acil olmayan durumlarda ise kara ambulansı ataması yapılır. Şehirde ki her bölgeye (düğüm noktasına) o bölgedeki ortalama olay sıklığı ve çok acil olay sıklığı sayıları ile orantılı kat sayı ataması yapılmıştır. İlk problem tipinde, kara ambulans sisteminin en iyi şekilde çalıştığı varsayılarak, sadece hava ambulanslarının, hastane (veya sıhhi bakım merkezlerine), çok acil olaylara en kısa toplam zamanda hizmet sağlayacak şekilde atanmasına çalışılmıştır. İkinci problem tipinde, çok acil ve normal servis taleplerinin sayılarının bilindiği varsayılarak, hem kara hem de hava ambulanslarının aynı zamanda ve birlikte en az toplam talep zamanını sağlayacak şekilde atanmasına çalışılmıştır.
Master of Science in Industrial Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2018. Supervisor: Prof. Dr. Bela Vizvari.
Keywords: Industrial Engineering; Emergency Services--Management--Planning; Response time; Aerial transportation; Emergency service; Genetic Algorithm